2020
DOI: 10.1590/1983-1447.2020.20190364
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the incidence and preventability of adverse events in hospitals: an integrative review

Abstract: Objective: To highlight the scientific production related to the use of the retrospective chart review methods to assess the incidence and preventability of adverse events in hospitals. Method: An integrative review in the MEDLINE, LILACS, SCOPUS, Web of Science and EMBASE databases conducted in May 2019 with the following guiding question: What is known about the retrospective chart review methods to assess the incidence and preventability of adverse events in hospitals? Subsequently, the categorization, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
(51 reference statements)
2
8
0
14
Order By: Relevance
“…Schwendimann et al’s scoping review [ 32 ] of multicentre studies reported a median of 10% of admissions with AEs, which is less than half what we found. But this is congruent with Zanetti et al’s integrative review, which reported between 5% and 11% [ 7 ]. Both of those reviews, especially Schwendimann et al’s, concentrated solely on studies applying the HMPS methodology, not TT methodology [ 7 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Schwendimann et al’s scoping review [ 32 ] of multicentre studies reported a median of 10% of admissions with AEs, which is less than half what we found. But this is congruent with Zanetti et al’s integrative review, which reported between 5% and 11% [ 7 ]. Both of those reviews, especially Schwendimann et al’s, concentrated solely on studies applying the HMPS methodology, not TT methodology [ 7 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Considering that approximately 40% of admissions can be associated with AEs, it is likely that the consequences, both on health care service costs and on patient suffering, are underestimated [ 4 , 5 ]. While some AEs are hardly avoidable, others are: studies have indicated that 6%–83% of AEs are deemed to be preventable [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…When passing vital signs thresholds, alarms were sent out to the nurses on a mobile device. These thresholds were based upon the conventional MEWS thresholds [ 3 ]. After receiving a vital signs alert, the nurses were asked to measure the patient’s vital parameters manually in accordance with the routine hospital policy; measuring all parameters for a MEWS score.…”
Section: Methodsmentioning
confidence: 99%
“…Serious unexpected adverse events and complications occur regularly on general surgical wards, especially in the group of high-risk postsurgical or elderly frail patients [ 1 3 ]. On general wards the current standard of care is intermittent monitoring of vital signs with Early Warning Scores (EWS), in which nurses play an important role in the measurement, recognition of possible deterioration, and follow-up [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, o foco na assistência isenta de danos ganhou notoriedade na década de 90 quando as instituições públicas e privadas almejaram a criação de estratégias com a finalidade de garantir assistência de qualidade aos pacientes Mesmo com a implementação das seis Metas internacionais de Segurança do Paciente, atualmente estabelecidas 7 metas, a incidência estimada para os eventos adversos tem se mantido elevada em instituições hospitalares com variação entre 5,4 a 14,2% segundo levantamento de 2004 a 2019 em uma revisão integrativa da literatura 5 . Além disso, de acordo com a Organização Mundial de saúde, existe uma carga econômica associada a erros de medicação que acarretou um custo global de 42 bilhões de dólares anuais 6 .…”
Section: Introductionunclassified